A informática no Brasil e o novo paradigma industrial - Mazzeo, Luzia Maria (1996)
The present thesis aims to identify and evaluate the impacts provoked by the end of informatics market reserve and the Brazilian open market policy in terms of the technology modernization and the information society. The overall object of this thesis is to analyse the news challenges that brazilian informatics industry will have to face, considering the emergency of a new model of international competition identified in the last decade and the transformations identified in Brazil in the begging of the 90's. This thesis also verifies the difficulties of the informatics companies and the informatics sector probable behaviour facing a new standard of international competition. In addition, the thesis identifies the development models and the foreign commerce policy identified in brazilian industrialization history. In terms of the new paradigm of industrial organization, the thesis objective is to identify the open economy and the new international order, making an analysis of transformations that are occurring in world wide. This analysis will be done through the critical revision of literature, exposing the thinking of some authors about the destituteness of 'old world order' and installation of 'new world order'. Finally, the study point out the impacts of open commerce concerning the informatics sector in Brazil.